Accommodating to motor difficulties and communication impairments in people with autism: the MORE intervention model - Emerson, Anne; Dearden, Jackie (Frontiers in Integrative Neuroscience, 2013)
Motor impairment in individuals with autism potentially impacts on their development in all spheres. This paper is particularly concerned with people with severe communication impairments suggesting that recognition of the impact of motor impairments on their lives could lead to more effective interventions being developed. One such intervention is the MORE (Means, Opportunities, Reasons and Expectations) model, founded on the ‘least dangerous assumption’, that is assuming competence until otherwise established through long-term observation and assessment. Components of the model include recognising the importance of having high expectations and linking this to the way people are spoken to; timing within an intervention and over long periods; the importance of eye-hand coordination and teaching independent pointing skills. It is suggested that literacy should be offered as an early step which could significantly enhance communication.